Advancing resveratrol delivery: protein-polysaccharide complexes as innovative nanocarriers - Kamdi, Seema; Dr. Laxmikant Zawar (Prospects in Pharmaceutical Sciences, 2025)
Resveratrol (RES) has garnered significant attention in the medical field because of its remarkable physiological benefits, including anticancer, antioxidant, anti-inflammatory, neuroprotective, cardioprotective, and antidiabetic properties. However, its development and application are hindered by poor water solubility, inconsistent and low oral bioavailability, and instability in chemical and biochemical environments. A novel biopolymer structure, the protein-polysaccharide (PRO-POL)-based delivery system, offers advantages, such as minimal toxicity, biocompatibility, biodegradability, and controlled release. Numerous studies have explored PRO-POL-based delivery systems to enhance RES bioavailability. This review examines the interactions between various proteins (e.g., gliadin, whey protein, soybean protein isolate, pea protein, and zein) and polysaccharides (chitosan, sodium alginate, and pectin) and their impact on size, surface charge, encapsulation efficiency, and release characteristics. This study highlights how PRO-POL-based delivery systems improve RES bioavailability. Additionally, it provides an overview of PRO-POL complexes incorporating RES, serving as a reference for the development and implementation of PRO-POL delivery systems.